FINANCIAL FRAUD AS A THREAT TO THE FINANCIAL SECURITY OF AN ENTERPRISE: MODERN CHALLENGES AND METHODS OF COUNTERACTION - BLYZNYUK, Tetyana; KYRII, Valentyna; HOLUBKIN, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article is devoted to an in-depth analysis of financial fraud, which poses a significant threat to the modern business environment. The rapid expansion of digital technologies and the globalization of the economy create new opportunities for attackers, which requires constant improvement of methods for monitoring and protecting financial transactions. The study aims to review modern monitoring methods and approaches to protecting electronic payments and develop practical recommendations for their improvement.The article analyzes in detail the latest research and publications related to the detection of financial anomalies, the application of machine learning algorithms, big data analysis, and other technological solutions. Various types of financial fraud are considered, including fraud with credit cards, financial statements, insurance, cryptocurrencies, and other digital assets. Special attention is paid to analyzing methods for managing the risks of financial transactions, including traditional and modern approaches, such as machine learning and artificial intelligence methods.The issues of real-time transaction monitoring and post-facto analysis are considered, as well as the importance of forming an explicit data structure and high-quality information collection to detect fraudulent schemes effectively. The conclusions emphasize the need for a multi-level transaction control system that combines preventive measures and in-depth data analysis. Integrating legislation and cooperation between financial institutions for effective counteraction to fraud is also emphasized.The article offers practical recommendations for improving financial security systems, focusing on adapting to rapidly changing technological and economic conditions. Prospects for further research in this area are considered, including integrating blockchain solutions, quantum cryptography methods, and other innovative technologies to increase the transparency and security of financial transactions.
Keywords: financial fraud; transaction monitoring; electronic payments; machine learning; artificial intelligence; cybersecurity; cryptocurrencies; risk management; financial security; digital technologies